Geographically Aware Information Access with Geoparsing, Geocoding, and Georeferencing - Samulenok, Lara; Rubin, Victoria L. (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This position paper reviews and exemplifies advances in geospatial information systems and applications involving geospatial information and natural language. We discuss the role of geographically aware information access in human information behaviours such as information seeking, retrieval, and use, and highlight the role of automation in enriching current geospatial metadata. Cet exposé de position dresse et illustre les avancées dans le domaine des systèmes d’information géospatiale et des applications faisant appel à de l’information géospatiale et au langage naturel. On discute du rôle de l’accès à de l’information géographique relativement aux comportements informationnels tels que la recherche, le repérage et l’utilisation et on présente le rôle de l’automatisation dans l’enrichissement des métadonnées géospatiales actuelles.